2021
DOI: 10.3389/fphar.2021.686360
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chinese Medicine Compound in the Treatment of Rheumatoid Arthritis on the Level of Rheumatoid Factor and Anti-Cyclic Citrullinated Peptide Antibodies: A Systematic Review and Meta-Analysis

Abstract: Objectives: To evaluate the current evidence whether Chinese medicine compound (CMC) can reduce the serum levels of rheumatoid factor (RF) and anti-cyclic citrullinated peptide antibodies (anti-CCP).Methods: We comprehensively searched PubMed, Embase, the Cochrane Library, China National Knowledge Infrastructure (CNKI), the Database for Chinese Technical Periodicals (VIP), and Wanfang data. We then performed a systematic review and meta-analysis of all randomized controlled trials (RCTs) assessing the CMC ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…A recent epidemiologic study showed RA affected about 1% of the world's population (McInnes and Schett, 2017). The morbidity of RA is highest at the age of 50, with female patients as the main population (van der Woude and van der Helm-van Mil, 2018). Women are three to four times more prone to develop the disease than men, with data demonstrating a progressive increase in the incidence of RA in females during the last decade (Myasoedova et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent epidemiologic study showed RA affected about 1% of the world's population (McInnes and Schett, 2017). The morbidity of RA is highest at the age of 50, with female patients as the main population (van der Woude and van der Helm-van Mil, 2018). Women are three to four times more prone to develop the disease than men, with data demonstrating a progressive increase in the incidence of RA in females during the last decade (Myasoedova et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Traditional Chinese Medicine (TCM) has shown advantages in the treatment of RA. Chinese medicine formula monotherapy or combined with Western medicine had better performance on improving clinical symptoms, preventing the disease progression, reducing serum rheumatoid factor and anti-cyclic citrullinated peptide antibodies, and improving the bone mineral density of RA than Western medicine monotherapy ( Cai, et al, 2018 ; Tang, et al, 2021 ; Zhang et al, 2022 ). But to date, there is no TCM clinical trial for RA in women.…”
Section: Introductionmentioning
confidence: 99%
“…Ein im Jahr zuvor publizierte Metaanalyse und Review, in der 65 chinesische Studien mit insgesamt 6099 Patienten eingeschlossen waren, gibt Hinweise darauf, dass die Kombination der chinesischen Phytotherapie mit der klassischen antirheumatischen Therapie bei RA-Patienten effektiver hinsichtlich der Senkung des Serumspiegels des Rheumafaktors (RF) und des Anti-CCP-Antikörpers sei als die Monotherapie mit westlicher Medizin. Ein Publikationsbias kann verantwortlich sein, da nur Studien mit positiven Ergebnissen zur chinesischen Phytotherapie eingeschlossen waren [32].…”
Section: Die Chinesische Phytotherapieunclassified
“…However, there are a limited number of clinical trials and thus the evidence is low. The previous meta‐analysis demonstrated that TCM may target the immune system and help alleviate RA through different mechanisms—for instance, to lower the levels of both RF and anti‐cyclic citrullinated peptides (anti‐CCP) [81], to help protect the bones and cartilages and reduce damages [82] and to decrease the disease activity [83]. As outlined, treating the disease is not the only goal.…”
Section: Clinical Trialsmentioning
confidence: 99%